Complex Symbols in English and Kurdish Grammar - Dilovan Sayfuddin Saady (Zanco Journal of Humanity Sciences)
A group of lexical items which are stored in the lexicon in a form of some symbols are called complex symbols .This research attempts to deal with transformational grammar relating to complex symbols. Complex symbol is a morpheme with a set of semantic and syntactic features. These features are :category ,inherent ,selectional and subcategorization features . As far as the literature review for this study ,this topic has not been written about by any researcher . It may not only be significant for a researcher to write about a topic which had been conducted in a way different from the way he is writing about .But it is also important for a researcher to write about those topics that have not been researched yet. This is a descriptive and qualitative  study .Finally ,it is concluded that as far as subcategorization feature , in Kurdish language ditransitive verbs are not subcategorised for two NP complements but it is for an NP and a Prep. P .In English language it is. In idioms of both Kurdish and English languages  ,selectional restrictions do not work and have no role. The inherent feature in Kurdish language seems to be similar to that of English language by assigning semantic roles to the lexical items.